PELAKSANAAN PENERIMAAN PESERTA DIDIK BARU (PPDB) MELALUI SISTEM ZONASI SMA NEGERI KEBAKKRAMAT TAHUN PELAJARAN 2018/2019 - Fitri Pramushintha; Muhammad Akhyar; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
The purpose of this research are to evaluate: (1) readiness to implement PPDB through a zoning system in Kebakkramat Senior Senior High School 2018/2019; (2) preparation of teachers, principals and vice principals before implementing PPDB through a zoning system; (3) preparation of students and parents in implementing PPDB through a zoning system; (4) supporting facilities and infrastructure in implementing PPDB through a zoning system; (5) the implementation of PPDB through a zoning system in Kebakkramat Senior High School 2018/2019; (6) student learning outcomes after implementing the PPDB zoning system; (7) students and parents satisfaction with the policy of implementing PPDB through the zoning system. This research was conducted at Kebakkramat Senior High School. This study used the CIPP model (Context, Input, Process, Product). The population of this study were teachers, principals, vice principals, students and parents. Data collection techniques used is questionnaires distributed to all respondents and interviewing some respondents. This research was included as fact finding research, which is why instrument reability test was not necessary. Score analysis in range of quality aspects determination for each evaluation components was based on certain criteria. This research shows results: (1) Kebakkramat Senior High School has implemented PPDB zoning system very well; (2) parents and students have a sufficient condition on implementation of PPDB policy; (3) PPDB has a good readiness on implementing the program through zoning system; (4) students and parents have a sufficient readiness in implementing PPDB policy; (5) the implementation of PPDB through the zoning system runs smoothly; (6) inhibiting factors in the implementation of PPDB through the zoning system is the difficult procedures for the students and parents; (7) PPDB policy through the zoning system narrows students’s school choices; (8) teachers experience obstacles in teaching zoned students; (9) after PPDB is implemented through zoning system, students have lower learning outcomes.